PEMBARUAN VISUAL LOGO HTII SEBAGAI UPAYA REBRANDING ORGANISASI PROFESI NON PROFIT - Amalia Setyowulan; Endah Setyaningsih; Asrullah Ahmad (Jurnal Bakti Masyarakat Indonesia, 2021)
Professional organization is a forum for the scientific community in a branch or across science and technology, or a field of professional activity guaranteed by the state to develop professionalism and professional ethics in society [1]. Some of the well-known professional organizations include the Indonesian Doctors Association (IDI), the Indonesian Teachers Association (PGRI), the Indonesian Architects Association (IAI). There are also specific professional organizations, including the Indonesian Interior Design Association (HDII), the Association of Indonesian Landscape Architects (IALI), and the Indonesian Illuminating Engineering Society (HTII). HTII was founded on 7 May 1991 in Jakarta, and is the only forum in the lighting sector in Indonesia. Currently HTII members are more specific, namely the professional circles of illuminating engineering. This is evidenced by the HTII social media which only has 213 followers, for some people this figure does sound a lot, but for an organization that was founded in 1991 this figure is felt to be very small. This can then become the basis for HTII to make efforts to introduce the name, image of the organization and vision mission that has been carried for a long time, in order to expand the network both from professionals, prospective young professionals and nonprofessionals who are interested in knowledge lighting. Rebranding is necessary because HTII already has a logo and visual identity but does not have other supporting media. On the other hand, the logo from HTII is also considered to lack good clarity in legibility in a certain size scale. For this reason, in this PKM, one of the rebranding efforts is to create a new logo design for HTII. Currently, 5 new logo designs have been produced, which are ready to be defined ABSTRAK:Organisasi profesi, merupakan wadah bagi masyarakat ilmiah dalam suatu cabang atau lintas ilmu pengetahuan dan teknologi, atau suatu bidang kegiatan profesi yang dijamin oleh negara untuk mengembangkan profesionalisme dan etika profesi dalam masyarakat [1]. Beberapa organisasi profesi yang sudah banyak dikenal antara lain Ikatan Dokter Indonesia (IDI), Persatuan Guru Republik Indonesia (PGRI), Ikatan Arsitek Indonesia (IAI). Terdapat juga organisasi profesi yang spesifik, antara lain Himpunan Desain Interior Indonesia (HDII), Ikatatan Arsitek Lanskap Indonesia (IALI), dan Himpunan Teknik Iluminasi Indonesia (HTII). HTII didirikan pada 7 Mei 1991 di Jakarta, dan merupakan satu-satunya wadah di bidang pencahayaan di Indonesia. Saat ini anggota HTII lebih ke kalangan spesifik saja yaitu kalangan profesional teknik iluminasi. Hal ini dibuktikan dengan media sosial HTII yang hanya memiliki 213 followers, bagi sebagaian orang angka ini memang terdengar banyak, namun bagi organisasi yang berdiri dari tahun 1991 angka ini dirasa sangat sedikit. Hal ini kemudian bisa untuk menjadi dasar bagi HTII untuk melakukan upaya dalam mengenalkan nama, citra organisasi dan visi-misi mulia yang diusung sejak lama, agar bisa memperluas jaringan baik dari kalangan profesional, professional muda dan non profesional yang tertarik akan ilmu pencahayaan. Rebranding diperlukan karena HTII sudah mempunyai logo dan identitas visual namun belum memiliki media-media pendukung lain. Di sisi lain logo dari HTII juga dianggap kurang memiliki clarity yang baik secara keterbacaan dalam skala ukuran tertentu. Untuk itu dalam PKM ini, salah satu upaya rebranding adalah dengan membuat desain logo baru untuk HTII. Saat ini telah dihasilkan 5 desain logo baru, yang siap untuk ditetapkan.